Do mismatches between teams affect the risk of injury in the Rugby World Cup? - Fuller, C. W.; Caswell, S. E.; Zimbwa, T. (Journal of Science and Medicine in Sport, 2010)
The aim of this study was to assess whether differences in competing teams' body mass and playing performance affected the risk of injury in rugby union. The study was a prospective, whole population survey of players representing all countries competing at the Rugby World Cup in 2007. The study design followed the consensus statement for epidemiological studies in rugby with the main outcome measures being the incidence and severity of match injuries. Differences in players' average body mass and mismatches in the teams' overall and match performances did not create greater risks of injury for the lighter or less successful teams competing at Rugby World Cup 2007.